Pilot RCT of a social media parenting intervention for postpartum mothers with depression symptoms. (27th May 2019) - Boyd, Rhonda C.; Price, Jordan; Mogul, Marjie; Yates, Tweety; Guevara, James P.
ABSTRACT: Objective : This pilot study describes the adaptation of a parenting group intervention for social media, and examines the feasibility, acceptability and initial outcomes of the adapted intervention for mothers with postpartum depression symptoms. Background : Postpartum depression can negatively affect parenting and the parent–infant relationship. Mothers with postpartum depression symptoms experience barriers to access in-person parenting interventions. Methods : A small, randomised controlled trial was conducted with an adapted parenting intervention delivered via social media (Facebook) or in-person for mothers who screened positive for depression in paediatric clinics. Parenting sense of competence, depression symptoms and intervention attendance and satisfaction were assessed. Twenty-four mothers (mean age 26 years; predominantly African American with limited economic resources) participated in the study. Results : Linear regressions showed that the social media group had significantly improved parenting competence and decreased depression severity when compared to the in-person group. Attendance in the social media group was high (83%), but extremely poor in the in-person group (3%). The mothers rated the intervention positively and the majority of the mothers participated by posting comments on the group page on social media. Conclusion : The findings suggest the feasibility and benefit of delivering a parenting intervention through social media for postpartum mothers with high levels of depression symptoms.